Pharmaceutico - Analytical Evaluation of Modified Dosage Forms of Gojihwadi Kwatha (AYUSHDHARA, 2023)
Cough is an ongoing problem that affects a large proportion of the human community leading them to seek medical attention. It has been identified as the sixth common reason for hospital outpatient department visits. In classics, descriptions of disease Kasa clearly correlate with bronchitis and its pathophysiology exactly correlates the mechanism of cough reflex. Ayurveda advocates certain remedies to cure and prevent such diseases. Hence the present study has been contemplated to evaluate and verify the effectiveness of the Classical Ayurvedic remedies with special reference to pathogens causing the respiratory tract infections. Among the latest Ayurvedic formulations the Gojihwadi Kwatha which was designed and developed by none other than the famous physician of this era the great Vaidya Yadavji Trikamji Acharya has been selected for the study. This present study entitled “Pharmaceutico-analytical evaluation of modified dosage forms of Gojihwadi Kwatha” was carried out with a view to standardize Gojiwadi kwath and prepare its modified forms viz. Gojihwadi syrup, Gojihwadi granules, and Gojihwadi kwath churna. 12kg Gojihwadi kwaath churna was prepared while 6-liter Gojihwadi syrup and 3 kg Gojihwaadi granules were prepared. Gojihwaadi syrup has viscosity of 34.62 cP, total sugar content of 85.07 %w/w, reducing sugar content of 1.42 %w/w, non-reducing sugar content of 83.65%w/w and pesticide residue value within limits of standard parameter. Gojihwadi granules have total sugar of 78.44%w/w, an average particle size of 34.70. Total bacterial count, Total fungal count, and specific pathogens (E. coli, Salmonella spp, S.aureus, and Ps.aeroginosa) were absent in Gojihwadi kwatha churna, Gojihwadi syrup and Gojihwadi granules. So, it can be concluded that all the modified dosage forms of Gojihwadi kwatha are safe to use.